Christians and Muslims in Nineteenth-Century China: Perspectives of Two Contemporary Journals. Issue 1 (2nd January 2018) - Vogel, Stuart
ABSTRACT: Throughout the nineteenth and early twentieth centuries, two journals stand out as primary sources of information about China. The Chinese Repository and The Chinese Recorder and Missionary Journal were edited by senior missionary scholars, who recorded observations of Chinese life and the development of the Church in China. While they make only scattered references to the Muslim population in China, these items are nevertheless significant indicators of the size, importance and nature of these Muslim communities. They also portray Christian attitudes to 'Mohammedans' and on occasions indicate Christian strategies of engagement with them. There was a particular burst of interest in 'Mohammedism' in the 1880s. However, engagement with the Muslim communities was never a priority for the Christian missionary force, as they were a distinct minority of the total Chinese population.